An Integrated AFS-Based SWOT Analysis Approach for Evaluation of Strategies Under MCDM Environment. Issue 2 (December 2018) - Singh, Sunil Pratap; Singh, Preetvanti
Abstract: This article outlines the development of a hybrid methodology aimed to help the policymakers in strategic planning. The proposed methodology integrates the axiomatic fuzzy set (AFS) theory, analytic hierarchy process (AHP), and the concept of simple additive weighting (SAW) to evaluate the strategies by strengths, weaknesses, opportunities, and threats (SWOT) analysis. The combination of AHP with SWOT yields analytically determined weights of the factors included in SWOT analysis. The SAW technique provides a flexible technique to obtain the final ranking of strategies in multi-criteria decision situations. In SAW, the strategies are described using the AFS-based AHP calculation framework for normalization and consistent ratings over the SWOT factors. The AFS theory is incorporated in the model to overcome the uncertainty and ambiguity in human decision-making processes. The proposed integrated methodology copes with the inconsistency caused by different types of fuzzy numbers and normalization methods required in solving multi-criteria decision-making (MCDM) problems. A real-world application is conducted to illustrate the utilization of the model to evaluate SWOT analysis and strategies for tourism development.